A parameterization of DNV-GL storm profile for the calculation of design wave of marine structures. (November 2019) - Laface, Valentina; Bitner-Gregersen, Elzbieta M.; Arena, Felice; Romolo, Alessandra
Abstract: This paper proposes a parameterization of the Det Norske Veritas and Germanischer Lloyd (DNV GL) storm profile for the development of analytical solution for the calculation of the associated return period. This solution allows the possibility of calculating the design wave for marine structures by means of a very simple approach. The basic concept is to substitute the sequence of actual storms at a given site with a sequence of trapezoidal storms (TS) defined on the basis of the DNV GL storm temporal evolution and derive analytically the return period referring to the TSs sequence. The DNV GL storm is represented by a trapezium which may be totally defined by means of three parameters: the trapezium height related to the storm intensity, and its minor and major bases, which represent two durations D p, D * pertaining to the maximum significant wave height H smax and to 50% of H smax, respectively. It is assumed that the parameters D p, D * are uncorrelated to the storm intensity and are the same for all the storms. With this assumption, the return period is obtained in a closed form as a function of the ratio n between D p and D *, D * itself, and of the exceedance probability distribution of significant wave height. The model is validated by comparison with Equivalent Triangular Storm (ETS) model by processing buoys data at four locations representative of different wave climates: Haltenbanken in North Sea, Alghero in Mediterranean Sea, stations 41001 and 46006 in Atlantic and Pacific Oceans, respectively. Results reveal that although its significant simplicity, the TS model provides reliable estimate of return values which are in agreement with those achieved by ETS model. Further, the employment of TS model with the values of parameters n and D * corresponding to the DNV GL profile is suitable for any location. Highlights: The paper proposes a parameterization of the DNV-GL storm profile, defined Trapezoidal Storm (TS) model. An analytical solution is derived for the return period of sea storms exceeding a fixed threshold. The TS solution is achieved as a function of the distribution of significant wave height at the site. The solution may be applied for calculating the design wave of marine structures.